EFEK KADMIUM TERHADAP KANDUNGAN PROTEIN, KARBOHIDRAT, DAN KALSIUM KERANG AIR TAWAR (Elongaria orientalis Lea, 1840) - , AKHMAD SYAKUR ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cadmium (Cd) is wide-spread metals in aquatic ecosystem. It has long half-life and toxic organisms. Aquatic animals uptake Cd through gills and digestive tract. Cd can inhibit enzym activities in protein and carbohydrate metabolism process. Cd also has been reported to interfere Ca homeostasis. Protein, carbohydrate, and calcium are important component in shell formation of mussels. The aims of this research are to study the effects of Cd on protein, carbohydrate, and calcium levels in the gills, mantle, digestive gland, and kidney of freshwater mussel Elongaria orientalis. Mussels were exposed to Cd via water (20 Âµg /L) for 24 days and 12 days of depuration. Mussels were diseceted of gills, mantle, digestive gland, and kidneys on day 0, 1, 6, 12, 18, 24 (exposure time) and day 30, 36 (depuration time). Protein level was determined by Bradford method, carbohydrate and Ca level being by Phenol-Sufuric acid method, and Atomic Absorbance Spectrophotometer (AAS). The result show that protein and carbohydrate levels decrease during Cd exposure. It is accompanied by increase of Ca concentration. However, during depuration time, protein and carbohydrate levels increase, while Ca concentration decrease.